Feedback-based control structure for frequency/voltage regulation using the state of electrical vehicle charge station and point estimation method. (June 2022) - Rajamand, Sahbasadat
Abstract: Electrical-vehicle-based microgrid (MG) has received much attention in new power systems. Cost reduction, voltage profile improvement and greenhouse gas reduction are some benefits available in these system. However, some challenges as electrical vehicle (EV) energy management, electrical vehicle charging station (EVCS) localization, supporting all load demands and voltage/frequency regulation are focused in new research issues. In other side, uncertainties of EVs, EVCS, PV/WT and loads must be analyzed in the MG to improve the performance in voltage and frequency regulation. Using the state of charge (SOC) in EVCS and feedback it to the control structure can enhance the performance of the MG in voltage and frequency regulation and stability. The effect of EVCS feedback on the control circuit is analyzed in this paper with combining of accurate estimated values of uncertain DGs and loads using point estimation method. Simulation results show significant improvement in frequency/voltage regulation in addition to the voltage profile and supported load using SOC of EV and EVCS in the control structure.